Width of the surface plasmon resonance line in spherical metal nanoparticles - Biliuk, A.A.; Semchuk, O.Yu.; Havryliuk, O.O. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2020)
In recent years, there has been increasing interest in the study of the optical properties of metallic nanostructures. This interest is primarily related to the practical application of such nanostructures in quantum optical computers, micro- and nanosensors. These applications are based on the fundamental optical effect of excitation of surface plasmons. Surface plasmons are electromagnetic excitations of the electron plasma of metals at the metal-dielectric interface, which are accompanied by fluctuations in the surface charge density. The consequence of this phenomenon is surface plasmon resonance (SPR) – an increase in the energy absorption cross-section of a metal nanoparticle as the incident light frequency (laser irradiation) approaches the frequency of the nanoparticle SPR. The SPR frequency for metallic nanoparticles in a dielectric matrix εₘ is found. Light-excited plasmon vibrations of conduction electrons in metallic nanoparticles located in a dielectric matrix will eventually attenuate due to various relaxation processes, in particular due to interaction of the conduction electrons with the crystal lattice (electron-phonon interaction) or due to electron-electron interaction at the surface of the nanoparticles, when the average free electron path in the nanoparticles exceeds its size. It defines the natural width of the SPR line. It has been shown that oscillations of the SPR line width can be observed in metallic nanoparticles with a change in the dielectric constant of the medium in which they are. The oscillations are well expressed in nanoparticles with smaller radii and disappear for nanoparticles of larger radii. The magnitude of these oscillations increases with decreasing nanoparticle radius and increases markedly with increasing the dielectric constant of the environment. В останні роки зріс інтерес до вивчення оптичних властивостей металевих наноструктур. Цей інтерес у першу чергу пов’язаний з можливістю практичного застосування таких наноструктур у квантових оптичних комп’ютерах, мікро- та наносенсорах. В основі цих застосувань лежить фундаментальний оптичний ефект збудження поверхневих плазмонів. Поверхневі плазмони – це електромагнітні збудження електронної плазми металів на границі метал–діелектрик, які супроводжуються флуктуаціями густини поверхневого заряду. Наслідком цього явища є поверхневий плазмонний резонанс (ППР) – зростання перерізу поглинання енергії металевою наночастинкою при наближенні частоти падаючого світла (лазерного випромінювання) до частоти ППР наночастинки. Знайдено частоту ППР для металевих наночастинок, що знаходяться в діелектричній матриці. Збуджені світлом плазмонні коливання електронів провідності у металевих наночастинках, що знаходяться в діелектричній матриці, з часом затухатимуть за рахунок різних релаксаційних процесів, зокрема за рахунок взаємодії електронів провідності наночастинок з кристалічною ґраткою (електрон-фононна взаємодія), або за рахунок розсіяння електронів на внутрішній поверхні наночастинки, коли середня довжина вільного пробігу електронів у наночастинці перевищує її розмір. Це зумовлює природну ширину лінії ППР. Показано, що в сферичних металевих наночастинках можуть спостерігатися осциляції ширини лінії ППР зі зміною діелектричної проникності середовища, в якому вони знаходяться. Осциляції добре виражені для наночастинок з меншими радіусами і зникають для наночастинок великих радіусів. Величина цих осциляцій збільшується зі зменшенням радіусу наночастинки і помітно зростає зі збільшенням діелектричної проникності оточуючого середовища.